2008
DOI: 10.1371/journal.pone.0003208
|View full text |Cite
|
Sign up to set email alerts
|

The Variability of the Harlequin Mouse Phenotype Resembles that of Human Mitochondrial-Complex I-Deficiency Syndromes

Abstract: BackgroundDespite the considerable progress made in understanding the molecular bases of mitochondrial diseases, no effective treatments have been developed to date. Faithful animal models would be extremely helpful for designing such treatments. We showed previously that the Harlequin mouse phenotype was due to a specific mitochondrial complex I deficiency resulting from the loss of the Apoptosis Inducing Factor (Aif) protein.Methodology/Principal FindingsHere, we conducted a detailed evaluation of the Harleq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
89
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 36 publications
11
89
0
Order By: Relevance
“…This probably reflects the comparative paucity of mitochondria in the brain, because the ratio of AIF protein and the most abundant outer mitochondrial membrane protein, VDAC, is similar in a panel of distinct mouse organs including brain. 14 The expression levels of AIF1-and AIF2-specific mRNAs were equivalent in the adult mouse brain and were similarly affected by the hypomorphic Hq mutation that reduced the expression of both AIF1 and AIF2 to around 20% of the control level (Figure 2d). It is noteworthy that the expression of human AIF2 mRNA was higher in adult brain than in fetal brain (while that of AIF1 was lower) (Figure 2b), indicating that the AIF1/AIF2 ratio decreases as brain cells differentiate.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This probably reflects the comparative paucity of mitochondria in the brain, because the ratio of AIF protein and the most abundant outer mitochondrial membrane protein, VDAC, is similar in a panel of distinct mouse organs including brain. 14 The expression levels of AIF1-and AIF2-specific mRNAs were equivalent in the adult mouse brain and were similarly affected by the hypomorphic Hq mutation that reduced the expression of both AIF1 and AIF2 to around 20% of the control level (Figure 2d). It is noteworthy that the expression of human AIF2 mRNA was higher in adult brain than in fetal brain (while that of AIF1 was lower) (Figure 2b), indicating that the AIF1/AIF2 ratio decreases as brain cells differentiate.…”
Section: Resultsmentioning
confidence: 91%
“…8 Knockdown, deletion or hypomorphic mutation of AIF (the harlequin or Hq mutation) reduces the expression of complex I subunits in the respiratory chain, 8 thereby provoking a mitochondriopathy that leads to progressive neurodegeneration, photoreceptor loss and cardiomyopathy. [9][10][11][12][13] The consistent finding that the targeting of AIF mostly affects the central nervous system (CNS) 9 might either be explained by the general tendency of complex I mitochondriopathies to manifest at the level of the CNS 14 and/or by an implication of AIF in the differentiation of neuronal cell precursors. 12 On apoptotic stimuli, AIF, which is able to directly interact with DNA, 15 translocates to the nucleus and participates in chromatin condensation and chromatinolysis.…”
mentioning
confidence: 99%
“…Apart from oxidative stress sensitivity, complementary observations have demonstrated that AIF-deficiency compromises oxidative phosphorylation. On the one hand, it seems that AIF is required for the assembly and stability of complex I and III of the mitochondrial respiratory chain (28,29). On the other hand, AIF deletion impairs the function of the respiratory chain via its role on maintaining mitochondrial morphology (8).…”
Section: Vital Function Of Aifmentioning
confidence: 99%
“…Hq/Y ) mouse, which has a loss of AIF protein of up to 80% relative to wild-type (WT) mice (13), has a decrease in complex I activity in a variety of organs (14,15), which is reminiscent of human complex I mitochondrial deficiency syndromes. Other studies (15) have also linked AIF to the stabilization, assembly, and activity of complex I.…”
mentioning
confidence: 99%